Pelatihan Strategi Pemasaran Online untuk Meningkatkan Daya Saing UMKM di Desa Situ Gadung Kabupaten Tangerang - Dewi Ningsih; Ali Zaenal Abidin; Budi Ismanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid advancement of digital technology presents new opportunities for micro, small, and medium enterprises (MSMEs) to expand their market reach, yet many MSMEs in rural areas such as Desa Situ Gadung, Tangerang Regency, face challenges in implementing effective online marketing, limiting their competitiveness. This community service activity aimed to enhance the online marketing capabilities of local MSME entrepreneurs to improve their business performance. Conducted on August 19, 2025, by a team of nine lecturers from Universitas Pamulang, the program involved 30 local traders near the school. The implementation followed three stages: preparation, execution, and reporting. During the execution, participants received material presentations, engaged in practical exercises, discussions, and question-and-answer sessions to deepen their understanding of digital marketing strategies. The results demonstrated a significant improvement in participants’ knowledge and skills regarding online marketing platforms, content creation, and online sales techniques, while also fostering confidence in applying these strategies to their businesses. The interactive approach facilitated problem-solving and knowledge sharing, contributing to the enhanced competitiveness of MSMEs in Desa Situ Gadung.